The Use Of Clock Replicas As An Effort To Improve The Understanding Of Class V Students' Odd Semester Of Sd Negeri 3 Kingkang Year 2013/2014 - Setiyowatik, Yuni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to apply the demonstration and assignment method to increase students' understanding of mathematics learning about angle sizes for class V elementary school students using the Cooperative Learning learning model assisted by Google Meet. The research carried out was Class Action Research (PTK) in two cycles, with each cycle consisting of two meetings. The stages of each cycle were Planning, Implementation, Observation and reflection. Each meeting carried out a pre-test and post-test to determine the students' progress. In the cycle In cycle I, 76% of students completed the post test. In cycle II, 90% of students completed the post test. These results indicate that the Cooperative learning model can improve students' understanding, especially Class V mathematics at SDN 3 Kingkang. Based on the results of research and discussion on the implementation of classroom action research at SD Negeri 3 Kingkang class V semester I 2013/2014